1995
DOI: 10.1007/bf01534377
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1?-induced neutrophil recruitment and acute lung injury in hamsters

Abstract: Administering recombinant interleukin-1 beta (IL-1 beta) intratracheally caused lung neutrophil accumulation and lung injury in hamsters. The percentage of leukocytes that were neutrophils increased progressively in lavages from lungs of hamsters given 25, 50, or 100 ng IL-1 beta intratracheally 2 h before. Lung injury, reflected by increased lung lavage protein concentrations and lung lavage hemoglobin concentrations, increased 2 h after administering 100 ng IL-1 beta. Lung injury, reflected by lung wet weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 17 publications
2
16
0
1
Order By: Relevance
“…In contrast, the extent of tissue damage in endotoxintreated mice, a model for sepsis-induced ARDS, was reduced by treatment with TNF-␣ antagonists. These results suggest that TNF-␣ may play an important role in lung injury induced by bacterial lipopolysaccharide (LPS), supporting a potential role for these cytokines at least in sepsis-induced ARDS (22,24,26,32), but may play less of a role in reovirus 1/L-induced ARDS as well as ARDS due to trauma or severe hemorrhage (21,25). However, whether the concentration of individual cytokines/chemokines is of a predictive value for either the development of or the recovery from ARDS remains controversial (1).…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, the extent of tissue damage in endotoxintreated mice, a model for sepsis-induced ARDS, was reduced by treatment with TNF-␣ antagonists. These results suggest that TNF-␣ may play an important role in lung injury induced by bacterial lipopolysaccharide (LPS), supporting a potential role for these cytokines at least in sepsis-induced ARDS (22,24,26,32), but may play less of a role in reovirus 1/L-induced ARDS as well as ARDS due to trauma or severe hemorrhage (21,25). However, whether the concentration of individual cytokines/chemokines is of a predictive value for either the development of or the recovery from ARDS remains controversial (1).…”
Section: Discussionmentioning
confidence: 97%
“…However, IL-1b is a direct product of LPS-dependent activation of the TLR4 pathway, and IL-1b gene expression has been identified as a common thread in multiple models of ventilator-induced lung injury. IL-1b causes neutrophil recruitment and injury in the lungs of hamsters (34,35), and there is evidence that early inflammatory responses in the lungs of humans with ARDS are predominantly attributable to IL-1b and not to IL-6 or TNF-a (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, the TNF-α/IL-1 associated neutrophilic exudate has been linked to an increased phagocytic capacity of the lung, with release of enzymes from neutrophils and with respiratory burst activity. The local release of enzymes from neutrophils probably makes important contributions to lung tissue injury and increased vascular permeability with resultant lung haemorrhages and edema [94,129]. In vitro studies have demonstrated stimulating effects of TNF-α and IL-1 on both neutrophils and macrophages of several animal species.…”
Section: Cytokine Effects On the Respiratory Tractmentioning
confidence: 99%